NEW DATA ON AGE AND NATURE OF CARBONIZATION WITHIN SOUTHERN FLANK OF THE BAIKAL LEDGE OF THE SIBERIAN CRATON BASEMENT - Yu. V. Danilova; V. B. Savelyeva; T. G. Shumilova; A. V. Ivanov; B. S. Danilov; E. P. Bazarova (Геодинамика и тектонофизика, 2017)
The Baikal ledge rock formations in the Siberian craton structure are included in the Akitkan mobile belt which is considered as the Late Paleoproterozoic independent island arc system moved up to the ancient basement during the terrains amalgamation 1.91–2.00 Ga ago (Fig. 1) [Rosen, 2003; Gladkochub et al., 2009; Didenko et al., 2013].